Distribution and safety assessment of heavy metals in fresh meat from Zhejiang, China - Jian Long Han; Xiao Dong Pan; Qing Chen (Scientific Reports, 2022)
Abstract There are increasing concerns on heavy metals in animal derived foods. We analyzed the levels of As, Cd, Cr, Cu, Hg, Ni, and Pb in 1066 fresh meat samples including pork, beef, mutton, chicken and duck from Zhejiang province, southeast China. The average levels of As, Cd, Cr, Cu, Hg, Ni, and Pb were 0.018, 0.002, 0.061, 0.801, 0.0038, 0.055, and 0.029 mg/kg wet weight respectively. There are significant positive correlations among Cd, Hg and Pb (P < 0.05) and negative correlations for Cu–Pb or Cu–Cd (P < 0.05). The exposure assessment showed that the health risk to humans by consuming these meat products was relatively low. However, regular monitoring of heavy metals in meat products is still recommended considering their intensive industrial activities.